Assessing Spatial-Temporal Patterns of Agricultural Drought Vulnerability and Its Impacts on Economic Crops, Nakhon Ratchasima, Thailand - Suwit Ongsomwang (Environment and Natural Resources Journal)
Thailand frequently suffers from rainfall shortages and ensuing droughts and the northeast region is especially vulnerable. The effects of climate change on water resources are further directly related to agricultural drought vulnerability. The objectives of the study were (1) to assess the spatial and temporal patterns of agricultural drought vulnerability based on agricultural drought exposure, agricultural drought sensitivity, and adaptive capacity and (2) to assess the potential impact of agricultural drought vulnerability on economic crops. To do so, this study integrated drought exposure, drought sensitivity and adaptive capacity for assessing spatial and temporal patterns of agricultural drought vulnerability and their potential impacts on economic crops at both the district and subdistrict levels in Thailand’s northeastern Nakhon Ratchasima Province.Our results showed that the spatial and temporal patterns of agricultural drought vulnerability in two periods (6m10 and 12m) varied from one region to another. Levels of severity were established, and moderate, high and very high levels were found in 10 districts and 96 subdistricts in the 6m10 period (May to October). They further occurred in 17 districts and 166 subdistricts in the 12m period (January to December). Districts and subdistricts with identical potential impact in both periods included 3 districts and 48 subdistricts. The potential impact of agricultural drought vulnerability on economic crops further was higher in the 12m duration than for 6m10. The highest potential impact was found to be on cassava (2023). In conclusion, the results of the study can be used as basic information for government agencies to monitor and mitigate agricultural drought in Nakhon Ratchasima. The government should further consider implementing a feasibility study for groundwater use in local agriculture, to better mitigate the impact of drought on important vulnerable economic crops.